Evaluation of technical drawing rules and its application in engineering drawings and final year projects - Sharifi, Mohammad Maruf (International Journal of Innovative Research and Scientific Studies, 2020)
The way of imagination and visualization of spatial, the ability of read, analyze and interpret different drawings for engineering students is provided by graphics training. The accurate way of technical drawings and rules in engineering drawing in final year projects are discussed in this paper. Primary and main material collection was done by distribution of questionnaires amongst the final year students and also by collecting their look outs based on a survey questionnaire amongst 300 students from different engineering departments. 300 different final year projects and 2500 engineering drawings were surveyed from a batch of students from 2016-0218. Although, the design drawings and architecture drawings in civil and architecture departments take around 90 sheets, whereas simple drawings are sparse. But in the field of geology and mind, oil and gas, hydraulics have majority of infrastructure and simpler drawings. Conclusively, the application of technical drawings is same in all departments, while in civil and Architecture department's projects, scales, thicknesses of lines, types of lines are used correctly and due to wrong use of symbols and colors is rejected. In Geology and mind, oil and gas and hydraulic due to the use of large scales, colors are accepted but, on basis of incorrect use of line thicknesses and small dimensions are rejected.